Factors Affecting The Activeness of Posyandu Cadres in The Working Area of The Pondok Meja Health Center in 2022 - Dame Try Lestari Saragih; M. Ridwan; Vinna Rahayu (Lembaga Pengembangan Kinerja Dosen, 2023)
Posyandu is the right health service for the Indonesian nation, and health service efforts needed by community members for the improvement of nutrition and health, as well as social welfare and improving the quality of human resources who are able to build and be able to help themselves, health services and management are carried out in a Puskesmas work area. The type of research used in this study is a type of quantitative research with a Cross sectional study approach. With the sampling technique in this study using purposive sampling. The number of samples in the study was 100 respondents with instruments used closed questionnaires. Data processing methods are carried out by editing, coding, data entry, data clening, data tabulation. Data analysis using univariate and bivariate. The results showed age (p-value = 0.001, PR 3.877), education (p-value = 0.028, PR 2.309), knowledge (p-value = 0.002, PR 3.259), completeness of facilities (p-value = 0.001, PR 3.252), health workers (p-value = 0.000, PR 4.237). Associated with the activeness of posyandu cadres with a p-vlue value of < 0.05. Keywords: Posyandu, Cadre Activity, Facility Completeness, Health workers